Membangun Kesadaran Finan Siswa Lewat Edukasi dan Sosialisasi di Sekolah - Surya Akbar; Riyan Pradesyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Independent Community Service Program (KKN) is a form of student community service that aims to apply knowledge practically in the field. This activity was carried out by students of the University of Muhammadiyah North Sumatra with the theme